A Survey of Pediatric CT Protocols and Radiation Doses in South Korean Hospitals to Optimize the Radiation Dose for Pediatric CT Scanning. Issue 50 (December 2015) - Hwang, Jae-Yeon; Do, Kyung-Hyun; Yang, Dong Hyun; Cho, Young Ah; Yoon, Hye-Kyung; Lee, Jin Seong; Koo, Hyun Jung
Abstract : Abstract: Children are at greater risk of radiation exposure than adults because the rapidly dividing cells of children tend to be more radiosensitive and they have a longer expected life time in which to develop potential radiation injury. Some studies have surveyed computed tomography (CT) radiation doses and several studies have established diagnostic reference levels according to patient age or body size; however, no survey of CT radiation doses with a large number of patients has yet been carried out in South Korea. The aim of the present study was to investigate the radiation dose in pediatric CT examinations performed throughout South Korea. From 512 CT (222 brain CT, 105 chest CT, and 185 abdominopelvic CT) scans that were referred to our tertiary hospital, a dose report sheet was available for retrospective analysis of CT scan protocols and dose, including the volumetric CT dose index (CTDIvol ), dose-length product (DLP), effective dose, and size-specific dose estimates (SSDE). At 55.2%, multiphase CT was the most frequently performed protocol for abdominopelvic CT. Tube current modulation was applied most often in abdominopelvic CT and chest CT, accounting for 70.1% and 62.7%, respectively. Regarding the CT dose, the interquartile ranges of the CTDIvol were 11.1 to 22.5 (newborns), 16.6 to 39.1 (⩽1 year), 14.6 to 41.7 (2–5 years), 23.5 to 44.1 (6–10 years), and 31.4 to 55.3 (⩽15 years) for brain CT; 1.3 to 5.7 (⩽1 year), 3.9 to 6.8 (2–5 years), 3.9 to 9.3 (6–10 years), and 7.7 to 13.8 (⩽15 years) for chest CT; and 4.0 to 7.5 (⩽1 year), 4.2 to 8.9 (2–5 years), 5.7 to 12.4 (6–10 years), and 7.6 to 16.6 (⩽15 years) for abdominopelvic CT. The SSDE and CTDIvol were well correlated for patients <5 years old, whereas the CTDIvol was lower in patients ≥6 years old. Our study describes the various parameters and dosimetry metrics of pediatric CT in South Korea. The CTDIvol, DLP, and effective dose were generally lower than in German and UK surveys, except in certain age groups.